2017
DOI: 10.1111/1467-9566.12617
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and the senses: a review

Abstract: Telemedicine technologies have been presented as solutions to the challenges of equitable, cost-effective and efficient health service provision for over two decades. The ways in which the sensory dimensions of medical care and the doctor-patient relationship are mediated via telemedicine can be important contributors to the success, failure or unintended consequences of telemedicine. In this article, we present a review of the relevant literature in social research that provides insights into the sensory dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 72 publications
0
59
0
6
Order By: Relevance
“…Recent studies have demonstrated that patients see the distancing effect of telemedicine as a benefit, feeling more comfortable discussing sensitive issues through a screen than in person with the doctor . But critics have advanced concerns that the move toward virtual clinicians will depersonalize medical interactions and erode authentic therapeutic relationships with patients . For example, some doctors have expressed concerns that the lack of physical touch and smell could affect their ability to make accurate diagnoses …”
Section: Using Social Media and Online Platforms To Improve Carementioning
confidence: 97%
“…Recent studies have demonstrated that patients see the distancing effect of telemedicine as a benefit, feeling more comfortable discussing sensitive issues through a screen than in person with the doctor . But critics have advanced concerns that the move toward virtual clinicians will depersonalize medical interactions and erode authentic therapeutic relationships with patients . For example, some doctors have expressed concerns that the lack of physical touch and smell could affect their ability to make accurate diagnoses …”
Section: Using Social Media and Online Platforms To Improve Carementioning
confidence: 97%
“…Telemedicine attempts to replicate the patient-to-doctor relationship in a realistic, productive manner. Transmitting sensory data over the Internet presents a primary challenge to the practice of telemedicine [5]. Lack of awareness and experience with the technology, along with uncertainties over how telemedical © 2018 The Author(s).…”
Section: Future Developments and Challengesmentioning
confidence: 99%
“…‘Telepsychiatry’ is a more contemporary instantiation of a (partial) psychiatric embracement of an external technological innovation; namely, telemedicine (APA, 2017b). Now a heterogeneous discipline encompassing an array of technologies and applications (Lupton and Maslen ), this was defined in the first editorial of the Telemedicine Journal as: ‘the delivery of care to patients anywhere in the world by combining communications technology with medical expertise’ (Goldberg : 1). For almost 30 years, clinicians and policymakers have advocated telemedicine as a means of containing healthcare costs and enhancing access (Lehous et al .…”
Section: Psychiatry and Technologymentioning
confidence: 99%